Sinus lift associated with second generation of autologous platelet concentrates : a systematic review - Otero, Ada Isis Pelaez (2021)
Introduction. The purpose of this systematic review was lift to analyze the available literature of clinical studies involving sinus lifting and comparing the efficiency of 2 nd autologous platelet concentrates (APC) generation related to its effects in bone gain and to clarify the regenerative efficacy of APC in sinus lift procedure, whether alone or as a coadjutant to other bone graft materials. Material and methods. This systematic review was conducted following the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines (1) with the focused question being determined according to the Population, Intervention, Comparison and Outcome, Follow-up (PICO) strategy.⁠ The protocol for this systematic review was registered on PROSPERO. The focused question for the present review was as follows: “In clinical studies with patients needing a maxillary sinus lift (P), does the use of ACPs either alone (I) or in conjunction with other biomaterials (C) improve the clinical outcome associated with bone gain and density (O), with at least 3 months of follow-up? An electronic search was conducted by two reviewers (A.I.P. and G.V.O.F.), independently, either electronic as manual search, through MEDLINE (PubMed), Science Direct, and Scopus databases with a platformspecific search strategy combining terms such as “sinus floor elevation”, “sinus augmentation”, “platelet-rich fibrin”, “second generation”, or “PRF”, and variables. Results. A total of 443 articles were obtained from the electronic database search, 67 on PubMed, 129 on Science Direct, and 247 on Scopus. An additional publication was considered from the manual search through the references of the included articles. After a full-text review, a total of 16 articles met all the criteria and were included in this review. Conclusion. Through the use of APCs in sinus augmentation the time required for bone graft maturation may be significantly reduced thus allowing sooner implant insertion, however overall long-term bone development did not show any significant difference.